Synthesis and Magnetic Properties of a Fe-Mn-Cr Multinuclear Complex with 4-Amino-1,2,4-triazole and Oxalate Ligands - Iis Siti Jahro; Djulia Onggo; Ismunandar Ismunandar; Susanto Imam Rahayu; Esther Jacoba Martha Vertelman; Petra van Koningsbruggen (Institut Teknologi Bandung, 2006)
A multinuclear Fe-Mn-Cr complex with 4-amino-1,2,4-triazole (NH2trz) and oxalate (ox) ligands has been synthesized successfully. The formula of the [Fe(NH2trz)3][ClO4][MnCr(ox)3].4H2O complex has been obtained based on the metal and C, H, N contents. The presence of water molecules, metal-ligand bonding and bridge ligand in the multinuclear complex has been confirmed by its infrared spectrum. The compound crystallizes in the hexagonal system with cell parameters of a = b = 18.695 Ã and c = 57.351 Ã . The compound shows a gradual spin crossover for iron(II) in the [Fe(NH2trz)3]2+ with transition temperature (T1/2) of 205 K. The antiferromagnetic interaction between Cr(III) and Mn(II) ions in the [MnCr(ox)3]n n- network is observed from the Weiss constant (Î¸) of -2.3 K.